A scale to measure nurses' and providers' patient centered care in primary care settings. Issue 12 (December 2019) - Radwin, Laurel E.; Cabral, Howard; Bokhour, Barbara G.; Seibert, Marjory Nealon; Stolzmann, Kelly; Annis, Ann; Mohr, David C.
Highlights: A new scale, the PC2:NaPS, measures patients' experiences of primary care. The PC2:NaPS uniquely assesses nurses' and providers' patient-centered care. The scale is reliable; acceptable fit statistics demonstrate construct validity. Two subscales measure nurses' contributions, and 1 measures providers' contributions. More precise attribution models may result when nurses' contributions are evaluated. Abstract: Objectives: 1) Refine pilot scale measuring patients' experiences of outpatient nurses' and providers' care; 2) Determine variance explained by (a) pilot scale items and (b) "Survey of Health Experiences of Patients" (SHEP)/"Consumer Assessment of Health Care Providers and Systems" (CAHPS) scale items. Methods: Randomly selected Veteran patients with recent visits with primary care outpatient nurses and providers (n = 1192) completed scales: pilot "PCC in Primary Care: Nurses and Providers Scale" and SHEP/CAHPS scale items. Factor analyses conducted using structural equation modeling (SEM), variance measurement using regression strategies. Results: SEM generated scale comprised 17 items in 3 factors; 2 operationalized nurses' care; 1 providers' care. Fit statistics were acceptable. Variance explained for total PCC: nurses = 42%, providers = 56%. Combined pilot and SHEP/CAHPS item analyses yielded similarly structured scale. 70% of provider care variance explained by single item. Conclusion: Appraisal of team, value-based care requires accrediting care to the appropriate clinician. The "PCC in Primary Care: Nurses and Providers Scale (PC 2 :NaPS)" provides a psychometrically sound measure for this purpose. Practice implications: PC 2 :NaPS use would improve primary care leaders' and clinicians' analyses of patient centered care and associated outcomes in their settings, and thus enhance success of quality improvement and organizational projects.